Adapting Inclusive Educational Models for Children with Physical Disabilities: Insights from a Special Needs School in Yogyakarta, Indonesia - Eko Setyo Wiyanto; Davin Eliandra Taluwara (Interdisciplinary Journal of Social Sciences, 2024)
This research explores the importance of inclusive education for children with disabilities, with a specific focus on educational models for children with physical disabilities (tuna daksa) in Indonesia. Education is recognized as a fundamental right for every individual, including those with special needs. The study employs a qualitative method, such as interviews, observations, and literature review, to analyze educational approaches at SLB Muhammadiyah Dekso, Yogyakarta. The key findings show that educational methods must be tailored to the specific needs of children with physical disabilities, including individualized approaches, the use of assistive devices, active learning methods, and emotional and social support. The research also identifies various challenges faced by teachers, such as communication barriers, lack of specialized resources, and inadequate school support. The author recommends increasing support and resources to create an inclusive and effective learning environment for all students, especially those with special needs.